(3JMaI GdYQhS heJYI GdfahSs - (3eMeO Hf CMeO GdHLGFj, CHh YHO Gddgs
(3ChdgG (B:s
(3GdMeO ddg GdPi ShZfG GdaVd LRjdG CeG HYO aEf Gddg JYGdi HdWa MceJg heG ChOi ai CHOGY GdYGde hYLGjH bOQJg Ndb GdEfSGf s
(3BNQgG (B:s
(3JSJZfi Hg Yf UjGfI LeGdgG hQhfb COGHgG hgfG GfJgi GdcdGe hGSJZaQ Gddg JYGdi hGSJbHd eeG NWJg jejfi hfWb Hg dSGfi hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3HChdgG YOI JedcGJ CbOegG SfI (B929s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdTjN eMeO SQhQ GdUHGf GdNGUI HecI GdecQeI (B((3COH (B78) s
Keywords: (3GdCOHs